Complete Decomposition of Formaldehyde at Room Temperature over a Platinum‐Decorated Hierarchically Porous Electrospun Titania Nanofiber Mat. Issue 7 (28th May 2014) - Nie, Longhui; Yu, Jiaguo; Fu, Junwei
Abstract To overcome the drawbacks of high air resistance and the need to be pressed into tablets or attached to other big‐block supports for powder catalysts in the application of air purification, a mat‐like hierarchically porous TiO2 nanofibers (TF) decorated with Pt nanoparticles (NPs) catalyst (Pt/TF) was synthesized by dipping the hierarchically porous TF mat fabricated by electrospinning into an H2PtCl6 solution followed by NaBH4 reduction. Such a mat‐like catalyst has a smaller air resistance than a powder catalyst because of its hierarchical macro‐/mesoporous structure and can be used directly in air‐purification systems because of its larger size. In addition, the as‐prepared Pt/TF catalyst showed enhanced catalytic activity compared to a Pt‐NP‐decorated commercial TiO2 (P25) catalyst in the decomposition of formaldehyde at room temperature because of its accessible Pt NPs and hierarchical porous structure that facilitates the diffusion of reactants and products. This work will provide some new insights into the design and fabrication of advanced catalysts for indoor air purification.